Gregatins, a Group of Related Fungal Secondary Metabolites, Inhibit Aspects of Quorum Sensing in Gram-Negative Bacteria - Beenker, Wouter A. G.; Hoeksma, Jelmer; den Hertog, Jeroen (Frontiers in Microbiology, 2022)
Quorum sensing (QS) is a process that regulates gene expression based on cell density. In bacteria, QS facilitates collaboration and it controls a plethora of pathways including biofilm formation and virulence factor production, which leads to lower sensitivity to antibiotics and higher toxicity in the host, respectively. Inhibition of QS is a promising strategy to combat bacterial infections. In this study, we tested the potential of secondary metabolites from fungi to inhibit bacterial QS using a library derived from more than ten thousand different fungal strains. We screened for QS inhibitors using Chromobacterium violaceum, leading to the identification of 39 active strains. These strains expressed two QS inhibitors that had been described before, providing proof-of-principle, as well as eight QS inhibitors that had not been described before. Further testing for QS inhibitor activity against the opportunistic pathogen Pseudomonas aeruginosa led to the identification of gregatins as an interesting family of compounds with QS inhibitor activity. Whereas various gregatins inhibited QS in P. aeruginosa, these gregatins did not inhibit virulence factor production and biofilm formation. We conclude that gregatins inhibit some, but not all aspects of QS.